Reading 'La Regenta' : Duplicitous discourse and the entropy of structure. - Sieburth, Stephanie A. (Purdue University monographs in Romance languages, 1990)
Criticism of La Regenta has until recently focused on the text's plot as an extraordinarily coherent and convincing fictional world. Stephanie A. Sieburth demonstrates that the devices which produce order in the text are counterbalanced by an equally strong tendency toward entropy of meaning. The narrator is shown to be duplicitous and unreliable in his judgments on characters and events. Without an omniscient narrator, readers must interpret for themselves the complex intertextual structure of the novel. Saints' lives, honor plays, and serial novels each provide partial reflections of Ana Ozo.